Artificial Ovary for Young Female Breast Cancer Patients - Chen, Jing; Torres-de la Roche, Luz Angela; Kahlert, Ulf D.; Isachenko, Vladimir; Huang, Hui; Hennefründ, Jörg; Yan, Xiaohong; Chen, Qionghua; Shi, Wenjie; Li, Youzhu (Frontiers in Medicine, 2022)
In recent decades, there has been increasing attention toward the quality of life of breast cancer (BC) survivors. Meeting the growing expectations of fertility preservation and the generation of biological offspring remains a great challenge for these patients. Conventional strategies for fertility preservation such as oocyte and embryo cryopreservation are not suitable for prepubertal cancer patients or in patients who need immediate cancer therapy. Ovarian tissue cryopreservation (OTC) before anticancer therapy and autotransplantation is an alternative option for these specific indications but has a risk of retransplantation malignant cells. An emerging strategy to resolve these issues is by constructing an artificial ovary combined with stem cells, which can support follicle proliferation and ensure sex hormone secretion. This promising technique can meet both demands of improving the quality of life and meanwhile fulfilling their expectation of biological offspring without the risk of cancer recurrence.